Idiopathic sclerosing encapsulating peritonitis: an uncommon cause of intestinal obstruction - José de Arimatéia Batista Araújo Filho; João Augusto Santos Martines; Brenda Margatho Ramos Martines; Adriano Ferreira Silva; Silvana Maria Lovisolo; Cláudio Campi de Castro (University of São Paulo, 2012)
Sclerosing encapsulating peritonitis (SEP), also called encapsulating peritonitis, is a rare and benign cause of intestinal obstruction of unknown etiology. Its onset may be acute or subacute although there are some reports with a two-month history. More commonly, this entity is secondary to chronic peritoneal dialysis, ventriculoperitoneal and peritoneovenous shunting, the use of β-blockers and systemic lupus erythematous. Recurrent episodes of bacterial peritonitis, intestinal tuberculosis, sarcoidosis, familial Mediterranean fever, gastrointestinal cancer, liver transplantation, intra-abdominal fibrogenic foreign bodies, and luteinized ovarian thecomas are also related to SEP. The idiopathic presentation is more rare. Abdominal pain, nausea, vomiting, weight loss, malnutrition, and clinically palpable mass characterize the clinical features. Diagnosis is frequently made with gross findings during surgery, imaging workup and histopathology. The authors report the case of a 36-yearold male patient with a 10-day history of abdominal pain that was operated on because of intestinal obstruction. Diagnosis was made preoperatively and confirmed by the intraoperative findings and histopathology.